Industrial Biotechnology Based on Enzymes From Extreme Environments - Mesbah, Noha M. (Frontiers in Bioengineering and Biotechnology, 2022)
Biocatalysis is crucial for a green, sustainable, biobased economy, and this has driven major advances in biotechnology and biocatalysis over the past two decades. There are numerous benefits to biocatalysis, including increased selectivity and specificity, reduced operating costs and lower toxicity, all of which result in lower environmental impact of industrial processes. Most enzymes available commercially are active and stable under a narrow range of conditions, and quickly lose activity at extremes of ion concentration, temperature, pH, pressure, and solvent concentrations. Extremophilic microorganisms thrive under extreme conditions and produce robust enzymes with higher activity and stability under unconventional circumstances. The number of extremophilic enzymes, or extremozymes, currently available are insufficient to meet growing industrial demand. This is in part due to difficulty in cultivation of extremophiles in a laboratory setting. This review will present an overview of extremozymes and their biotechnological applications. Culture-independent and genomic-based methods for study of extremozymes will be presented.